Clinical Assessment of Biphasic Calcium Phosphate in Granules and Paste Forms in Human Maxillary Sinus Bone Augmentation: A Randomized, Split-Mouth Clinical Trial - Bonardi, João Paulo [UNESP]; Pereira, Rodrigo dos Santos; Mourão, Carlos F.; Coelho Mendes, Bruno [UNESP]; Lowenstein, Adam; Montemezzi, Pietro; Giubilato, Flavio [UNESP]; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (MDPI, 2023)
The aim of the present study is to compare the biphasic calcium phosphate (BCP) using two different forms—(1) granules and (2) paste—in human maxillary sinus bone reconstruction as a split-mouth study using histomorphometric and immunolabeling for osteocalcin. Ten patients with bilateral maxillary posterior partial edentulism were selected in order to reconstruct bone height. They were divided into two groups: BCPG and BCP-P. After six months of bone healing, biopsies were harvested to assess the new bone formation and immunostaining for osteocalcin. The BCP g group had the following results: mean of bone formation in pristine bone 49.4 ± 21.6%, intermediate 49.4 ± 16.2%, and apical 55.3 ± 21.4%. The group BCP-P had a mean of 41.9 ± 17.3% in the pristine bone region, 37.5 ± 7.8% for intermediate, and 39.0 ± 13.5% for apical. The osteocalcin immunolabeling was high for both groups, demonstrating bone calcification. Thus, the two biomaterials present suitable results for the placement of dental implants.
Keywords: biomaterials; bone substitutes; sinus floor augmentation